Discovery Learning to Increase Motivation in Writing Indonesian Students of Education FKIP UMSU - Lestari P., Oktavia (Budapest International Research and Critics University, 2020)
In the learning process, there are many students who do not pay attention to the lessons delivered by the teacher. This is because students have very little interest in the subject. Students who are classified as few because many students like the lessons to be studied. To foster motivation so that students can be interested in these lessons. It is hoped that it can motivate students in writing. By using discovery learning model that emphasizes understanding and ideas that students will be interested in following the lesson well so that the expected learning achievement can be achieved. Education is a conscious effort that involves educators and students to carry out the learning process, in this case students are actively involved in order to be able to develop their potential to think and understand learning concepts and be able to apply them in everyday life. So, discovery learning can be used in any learning process, especially when later students will become teachers and can practice with students at school. This study aims to determine discovey learning to increase writing motivation, as a sample of two classes taken randomly, one class as an experimental class and the other class as a control class. The research variables are discovery learning and writing motivation.